James Meade, public ownership, and the idea of a citizens' trust. (29th March 2019) - O'Neill, Martin; White, Stuart
James Meade argued that public ownership of productive assets should have a central role in a 'liberal socialist' economy. While somewhat sceptical of the state seeking to run specific firms or industries, Meade argued that the state should own a significant share of a society's productive assets, using the return on the assets to promote a more equal distribution of income (e.g., through payment of a universal social dividend). This paper traces the development of Meade's thinking around this citizens' trust concept; explores its influence in UK policy discussions; and makes the case for the continuing relevance of the proposal in response to contemporary economic developments.